Structural and functional restoration by collateral sprouting of hippocampal 5-HT axons. - Azmitia, E; Buchan, A; Williams, J (1978)
The ability of the infracallosal 5-HT axons to assume the function of the supracallosal 5-HT axons in restoring symmetry in turning behaviour suggests that the function performed by these fibres is not unique to either projection. This situation is similar to that found by Langley for autonomic nerve fibres in the peripheral nervous system. He concluded 'that the function of any autonomic nerve fibre depends not so much upon its inherent properties as upon the nerve cells with which it has an opportunity of becoming connected in the process of development'. Thus, the function of the serotoninergic nerve fibres in the central nervous system may depend on the inherent properties of the neural systems with which they connect. This could explain why manipulation of whole brain 5-HT influences such a large number of behaviours. For instance, 5-HT has been shown to be involved in the regulaton of sleep, temperature, pain, aggression, locomotor activity, self-stimulation, sexual behaviour, avoidance-learning and water consumption. Thus it is possible that any one of these behaviours may be selectively modulated by the localised manipulations of 5-HT within the brain structure subserving that particular behaviour.